Folate intake and the risk of oral cavity and pharyngeal cancer: A pooled analysis within the International Head and Neck Cancer Epidemiology Consortium. Issue 4 (7th July 2014) - Galeone, Carlotta; Edefonti, Valeria; Parpinel, Maria; Leoncini, Emanuele; Matsuo, Keitaro; Talamini, Renato; Olshan, Andrew F.; Zevallos, Jose P.; Winn, Deborah M.; Jayaprakash, Vijayvel; Moysich, Kirsten; Zhang, Zuo‐Feng; et al.
<x xml:space="preserve">Abstract</x> There are suggestions of an inverse association between folate intake and serum folate levels and the risk of oral cavity and pharyngeal cancers (OPCs), but most studies are limited in sample size, with only few reporting information on the source of dietary folate. Our study aims to investigate the association between folate intake and the risk of OPC within the International Head and Neck Cancer Epidemiology (INHANCE) Consortium. We analyzed pooled individual‐level data from ten case–control studies participating in the INHANCE consortium, including 5, 127 cases and 13, 249 controls. Odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) were estimated for the associations between total folate intake (natural, fortification and supplementation) and natural folate only, and OPC risk. We found an inverse association between total folate intake and overall OPC risk (the adjusted OR for the highest vs. the lowest quintile was 0.65, 95% CI: 0.43–0.99), with a stronger association for oral cavity (OR = 0.57, 95% CI: 0.43–0.75). A similar inverse association, though somewhat weaker, was observed for folate intake from natural sources only in oral cavity cancer (OR = 0.64, 95% CI: 0.45–0.91). The highest OPC risk was observed in heavy alcohol drinkers with low folate intake as compared to never/light drinkers with high folate (OR = 4.05, 95% CI: 3.43–4.79); the attributable proportion (AP) owing to interaction was 11.1% (95% CI: 1.4–20.8%). Lastly, we reported an OR of 2.73 (95% CI:2.34‐3.19) for those ever tobacco users with low folate intake, compared with nevere tobacco users and high folate intake (AP of interaction =10.6%, 95% CI: 0.41‐20.8%). Our project of a large pool of case–control studies supports a protective effect of total folate intake on OPC risk.